2019
DOI: 10.1016/j.energy.2019.115933
|View full text |Cite
|
Sign up to set email alerts
|

Exergetic, economic and carbon emission studies of bio-olefin production via indirect steam gasification process

Abstract: The indirect steam gasification of biomass to olefins (IDBTO) coupled with CO2 utilization was proposed and simulated. Energy and exergy efficiencies, net CO2 emissions, and economic evaluation were performed against IDBTO as well as the direct oxygen-steam gasification of biomass to olifins (DBTO).The influences of unreacted gas recycling fraction (RU) and CO2 to dry biomass mass ratio (CO2/B) on the thermodynamic performance of the processes were also studied. The results showed that the yields of olefins of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…This option, which allows producing chemicals such as olefins, DME and methanol, can be considered environmentally sustainable and is generally preferred over other treatments (e. g., incineration) to deal with solid waste [136] . Similar approaches were recommended by Jiang et al., [129] who used biomass as the starting raw material, and Peters et al., [137] who proposed using manure and municipal solid waste as feedstock for CO 2 in Power‐to‐Gas projects. The use of liquid manure for this purpose would result in not only a reduction of CO 2 emissions (the authors report a net value of −85.6 gCO2 per MJ of generated fuel), but also reducing acidification and eutrophication of soil and water by avoiding land spreading this material.…”
Section: Environmental Impacts and Benefits Of Producing The Identifimentioning
confidence: 99%
See 2 more Smart Citations
“…This option, which allows producing chemicals such as olefins, DME and methanol, can be considered environmentally sustainable and is generally preferred over other treatments (e. g., incineration) to deal with solid waste [136] . Similar approaches were recommended by Jiang et al., [129] who used biomass as the starting raw material, and Peters et al., [137] who proposed using manure and municipal solid waste as feedstock for CO 2 in Power‐to‐Gas projects. The use of liquid manure for this purpose would result in not only a reduction of CO 2 emissions (the authors report a net value of −85.6 gCO2 per MJ of generated fuel), but also reducing acidification and eutrophication of soil and water by avoiding land spreading this material.…”
Section: Environmental Impacts and Benefits Of Producing The Identifimentioning
confidence: 99%
“…Methanol to olefins is a widely studied alternative that has started to be applied at large scale. The first commercial methanol‐to‐olefins plant was launched in 2010 in China, with a production rate of 600 kt y −1 [129] …”
Section: Environmental Impacts and Benefits Of Producing The Identifimentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the syngas composition and cold gas efficiency, thermodynamic modelling of char gasification using CO 2 was carried out using Aspen Plus (Li et al 2014). Detailed simulation descriptions can be found in our previous work (Jiang et al 2019(Jiang et al , 2020. The CGE represents conversion of the char energy content to the lower heating value of syngas, as defined by Eqs.…”
Section: Aspen Plus Simulationmentioning
confidence: 99%
“…While TEA of ethylene production via bioethanol dehydration with different sources revealed that not all scenarios enable the cost-competitive production of ethylene at current market prices [15 , 21] . Jiang et al [22] proposed bioolefin production via MTO coupled with the CO 2 utilization process and studied the exergetic, economic and carbon emission profiles. These design concepts or suggestions are positive to promote the development of certain renewable pathways.…”
Section: Introductionmentioning
confidence: 99%